The state's organizational capacity : prerequisites for economic development and political stability in Zaire and South Africa. - Kalombo, Gaston (My University, 1997)
It is widely assumed that the development of a country depends generally on the organization and the management of the state apparatus. Ostensibly the relative development of South Africa and the underdevelopment of Zaire would seem to confirm this. This study sets out to examine the validity of these assumptions by investigating the way the state apparatus is organized in Zaire and South Africa. The central role the state has played in the developmental process is the main concern of this thesis. The thesis attempts to understand this process through an in- depth investigation of the political and economic framework in both countries. It will present its arguments in five parts. The first outlines the conceptual framework necessary to compare and evaluate the political institutions by establishing the distinction between a "soft state" and a "hard state". The second part deals with the political system of both countries and the third contains an empirical analysis of their economic structure. The fourth provides a comparative institutional and process analysis of the state’s capabilities in Zaire and South Africa and largely emphasizes the state’s organizational strategies adopted to solve problems. A brief conclusion supplies an overall comparison and explanation of relative state capacity in the two countries and the consequences for development in each case of the state’s degree of competence.
A dissertation submitted to the Faculty of Arts at the University of the Witwatersrand, Johannesburg, for the Degree of MASTER OF ARTS.
Keywords: South Africa -- Politics and government.; Zaire -- Politics and government.